Mitigasi Risiko Non Performing Financing Produk Perbankan dengan Prinsip 5C - Rohmawati, Nur Khoiriyah; Dahruji, Dahruji (Forum Kerjasama Pendidikan Tinggi, 2024)
The development of musharaka financing in Indonesia continues to increase. The high use of musyarakah products is also accompanied by high risks faced by banks, especially financing risks which can be detrimental to the bank. The level of customer success in fulfilling their obligations can be seen from the Non-Performing Financing (NPF) indicator. BPRS Lantabur Tebuireng Lamongan branch experiences instability in the NPF value, which means it often experiences financing problems. In this case, appropriate risk prevention or mitigation efforts need to be made to maintain the NPF value. This research aims to determine the risks in musyarakah financing and analyze risk mitigation carried out by BPRS Lantabur Tebuireng Lamongan branch as an effort to prevent problematic financing. This research uses a qualitative approach with descriptive analysis methods and uses two data sources, namely primary data obtained through interviews and secondary data from related literature. The results of this research show that the risks that often occur in musyarakah financing are business risk and character risk. Risk mitigation efforts carried out by BPRS Lantabur Tebuireng Lamongan branch are by actively implementing the 5c principles, which consist of character, capacity, capital, collateral and conditions of economy. The assessment of the principles of capital, collateral and economic conditions at the BPRS Lantabur Tebuireng Lamongan Branch has been carried out well by implementing several fairly strict provisions, but an in-depth analysis needs to be carried out by the bank on the principles of character and capacity. This is because the risks that often occur in musyarakah financing are due to the customer's poor character and the customer's lack of ability in managing their business so that cases often occur that are detrimental to the bank.